Persistent hematospermia: seminal vesicle bleed*. (2nd April 2020) - Phan, Yih Chyn; Mahmalji, Wasim
Abstract: A 65-year-old gentleman, with no past medical problems and not on any anticoagulation was seen in the urology clinic with persistent hematospermia for the last few years. A thorough history and examination including a digital examination of the prostate was unremarkable. Bleeding from his female partner was also ruled out. Investigations such as prostate specific antigen (PSA) blood test, urine culture, semen culture, and flexible cystoscopy were performed, and these investigations were also within normal limits. Due to his persistent hematospermia even after masturbation, a magnetic resonance imaging (MRI) of his pelvis was performed to rule out any sinister intrapelvic pathology. His MRI pelvis revealed a right seminal vesicle haemorrhage which was the cause of his hematospermia. He was treated conservatively with the advice to abstain from ejaculation for a few months. More importantly, we have also reassured the patient.